Characteristics of climate change refugia for Australian biodiversity. (5th May 2014) - Reside, April E.; Welbergen, Justin A.; Phillips, Ben L.; Wardell‐Johnson, Grant W.; Keppel, Gunnar; Ferrier, Simon; Williams, Stephen E.; VanDerWal, Jeremy
Abstract Identifying refugia is a critical component of effective conservation of biodiversity under anthropogenic climate change. However, despite a surge in conceptual and practical interest, identifying refugia remains a significant challenge across diverse continental landscapes. We provide an overview of the key properties of refugia that promote species' persistence under climate change, including their capacity to (i) buffer species from climate change; (ii) sustain long‐term population viability and evolutionary processes; (iii) minimize the potential for deleterious species interactions, provided that the refugia are (iv) available and accessible to species under threat. Further, we classify refugia in terms of the environmental and biotic stressors that they provide protection from (i.e. thermal, hydric, cyclonic, pyric and biotic refugia), but ideally refugia should provide protection from a multitude of stressors. Our systematic characterization of refugia facilitates the identification of refugia in the Australian landscape. Challenges remain, however, specifically with respect to how to assess the quality of refugia at the level of individual species and whole species assemblages. It is essential that these challenges are overcome before refugia can live up to their acclaim as useful targets for conservation and management in the context of climate change.